Guillain–Barré Syndrome and Variants Following COVID-19 Vaccination: Report of 13 Cases - Kim, Jee-Eun; Min, Young Gi; Shin, Je-Young; Kwon, Young Nam; Bae, Jong Seok; Sung, Jung-Joon; Hong, Yoon-Ho (Frontiers in Neurology, 2022)
Background Amidst growing concern about an increased risk of Guillain–Barré syndrome (GBS) following COVID-19 vaccination, clinical and electrodiagnostic features have not been fully characterized. Methods We retrospectively reviewed medical records of the patients diagnosed with GBS and its variants following COVID-19 vaccination at four referral hospitals during the period of the mass vaccination program in South Korea (February to October 2021). Results We identified 13 patients with GBS and variants post COVID-19 vaccination: AstraZeneca vaccine (Vaxzevria) in 8, and Pfizer-BioNTech vaccine (Comirnaty) in 5. The mean time interval from vaccination to symptom onset was 15.6 days (range 4–30 days). Electrodiagnostic classification was demyelinating in 7, axonal in 4 and normal in 2 cases. Clinical manifestations were diverse with varying severity: classical GBS in 8 cases, paraparetic variant in 3, Miller-Fisher syndrome in 1 and acute cervicobrachial weakness in 1. Four patients developed respiratory failure, and 2 of them showed treatment-related fluctuations. Conclusion Our observations suggest that COVID-19 vaccines may be associated with GBS of distinctive clinical features characterized by severe quadriplegia, disproportionately frequent bilateral facial palsy or atypical incomplete variants. Continuous surveillance and further studies using robust study designs are warranted to fully assess the significance of the association.